SCHOOL COEXISTENCE IN THE FRAMEWORK OF UNDERSTANDING EDUCATIONAL REALITIES IN PHYSICAL EDUCATION CLASSES - Eduard Nariño; Henry López Beltrán; Mónica Lizett Forero Amaya (LÍNEA IMAGINARIA, 2025)
School coexistence within the framework of understanding the educational realities in physical education classes is a fundamental aspect for promoting inclusive, respectful, and collaborative learning environments. Physical education, as a discipline that fosters social interaction, teamwork, and the appreciation of diversity, becomes a favorable space for strengthening the values of respect, tolerance, and empathy among students. In a broader sense, this article aims to analyze the development of school coexistence from the perspective of the educational realities in physical education classes. In this sense, this essay concluded that promoting school coexistence that is aware of educational realities requires an institutional commitment that supports inclusive and reflective pedagogical practices. It is essential that both teachers and students actively participate in processes of dialogue and the joint construction of shared norms and values. Physical education, as a key educational space, can be a catalyst for strengthening positive bonds and consolidating a school culture where mutual respect and appreciation of diversity prevail.